KARAKTERISASI KITOSAN KOMBINASI CANGKANG KERANG HIJAU (Perna viridis) DAN CANGKANG RAJUNGAN (Portunus pelagicus) ASAL BANTEN, INDONESIA - Rifki Prayoga Aditia; Ginanjar Pratama; Aris Munandar; Dini Surilayani; Sakinah Haryati; Julian Alifka Rizky; Afifah Nurazizatul Hasanah; Bhatara Ayi Meata; Devi Faustine Elvina Nuryadin (Jurnal Perikanan dan Kelautan, 2022)
Green mussel shells (Perna viridis) and crab shells (Portunus pelagicus) have not been optimally utilized. It’s can be used as chitosan. Chitosan from green mussels has a low degree of deacetylation, so it needs to be combined with crab shells in its manufacture. The aims of this study were to characterize and determine the best combination of raw materials for making chitosan from green mussel shells and crab shells. The method in this study used a completely randomized design with triplicate. The treatment in this study was a combination of raw materials from green mussel shells and crab shells, which were 100:0; 75:25; 50:50% (w/w). The results of this study showed that the combination of green mussel shells and crab shells 50:50% (w/w) resulted the best characterization of chitosan with a yield 12.56%, water content 7.55%, ash content 1.59%, degree of deacetylation 73.96% and viscosity of 279 cP